La contrariedad complementaria entre las culturas de Europa, de África y de Asia, en la base de América - Beck, Heinrich (Revista Española de Pedagogía, 2016)
The cultural being of the human person and the specific cultures are related as the whole and the part. There is a complementary and contrary opposition among all the cultures, being necessary to look for its active integration. The paper studies the relationship between culture and nature in order to know if there is a global dynamic of sense that could be the basis of interculturality, analyzing the constitutive elements of each of the main world cultures.
Keywords: Revista Española de Pedagogía